Kontroversi Ajaran Syekh Siti Jenar: Analisis Teologis dan Respons Ulama Ahlussunnah wal Jamaah: The Controversial Teachings of Syekh Siti Jenar: A Theological Analysis and the Response of Ahlussunnah wal Jamaah Scholars - Muhammad Istiqamah; Indo Santalia; Mahmuddin (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This study critically examines the controversial teachings of Syekh Siti Jenar in the history of Islamic thought in Java, particularly his doctrine of Manunggaling Kawula Gusti and its implications for the purity of Islamic monotheism. The purpose of this research is to analyze Syekh Siti Jenar’s theological doctrines from the Ahlussunnah wal Jamaah (Aswaja) perspective, to identify the theological arguments behind the Aswaja scholars’ rejection of his ideas on wahdat al-wujud and his dismissal of Islamic law, and to assess its socio-religious consequences in the development of Islam in Java. This study employs a qualitative-descriptive method with a theological-historical approach based on library research using classical and modern references. The findings reveal that Siti Jenar’s teachings contradict the Aswaja doctrine of tanzih by blurring the ontological distinction between the Creator and His creation, and his rejection of formal worship has been deemed to potentially disrupt social order and religious authority. This research contributes to reinforcing the epistemological boundary between orthodox Sunni Sufism and extreme philosophical mysticism, while enriching the study of Aswaja theology in responding to Javanese spiritual phenomena in the Indonesian Islamic context.